ҚАРАҚАЛПАҚ ТИЛИНИҢ АРҚА ДИАЛЕКТИНДЕ МАЛ ШАРЎАШЫЛЫҒЫНА БАЙЛАНЫСЛЫ ҚОЛЛАНЫЛАТУҒЫН КӘСИПЛИК СӨЗЛЕР - Қурбанбаева, Б.Р. (SCIENCE and SOCIETY, 2021)
The article analyzes the use of professional words in the northern dialect of the Karakalpak language related to the animal husbandry in comparison with the modern Karakalpak literary language. Professional words of dialectical character were analyzed in terms of structure and meaning.